Airports, cultural gates: the case of inovative cities of Pekin and Hong Kong (2019)
Large airport projects, such as those in Beijing Daxing and Hong Kong, arise from the need to have efficient, sustainable spaces that have the capacity to house and offer services to passenger and visitor flows. In them, a great challenge is engineering, which must design each function to meet these expectations with excellence; but, understanding that these buildings constitute the doors to the nation, they cannot be limited to the functional scope. This is why the aesthetics, architecture and attention to detail are justified, which ultimately ensures that each visitor has a touch of culture.